Temperature-Based Grapevine Ripeness Modeling for cv. Touriga Nacional and Encruzado in the Dão Wine Region, Portugal - Pedro Rodrigues; Vanda Pedroso; Fernando Gonçalves; Samuel Reis; João A. Santos (Agronomy, 2021)
In the present study, we calibrated and validated thermal models to predict the DOY date at which the grape maturity index, potential alcohol/total acidity (PA/TA), reaches 0.75 (MS0.75), 1.0 (MS1), 1.5 (MS1.5), and 2.0 (MS2) for two grapevine Portuguese varieties, Touriga Nacional (TN) and Encruzado (EN), growing in the Dão wine region, Portugal. Daily rates of forcing calculated with the Sigmoid (SM) function and the Degree Day (DD) function were used. The outcomes show that the best performance of the models was obtained for the heat accumulation starting at flowering (tx = EL23). The analysis of model sensitivity to changes in forcing rate coefficients (T0, e, and d) enabled the selection of the same models for all maturity stage of each variety. The selected models revealed significant predictability, though dependent on the grape maturity stage and variety (EFF > 0.81 for TN and EFF > 0.75 for EN). The non-linear regression analyses of sugar concentration (SC) and total acidity (TA) with heat accumulation, calculated using the select models, demonstrated that a high fraction of SC and TA variance was explained by the variation of these temperature-based indices. Comparatively to SC and TA, the results highlight that the thermal conditions accumulated from flowering had a lower influence on pH juice variance.